Answer:
a = 1.5
b = 1.75
Explanation:
First, we need to solve
and replace the result in the initial equation as:
![x^2+3x+4=(x+a)^2+b\\x^2+3x+4=x^2+2ax+a^2+b](https://img.qammunity.org/2021/formulas/mathematics/high-school/niw22shxyrmfi6h2wrc6go89gm1c4rp6gp.png)
Then, this equality apply only if the coefficient of
is equal in both sides and the constant is equal in both sides.
It means that we have two equations:
![3x=2ax\\4=a^2+b](https://img.qammunity.org/2021/formulas/mathematics/high-school/rynknew6hqmcgffaao0fv880gsp226mzku.png)
So, using the first equation and solving for a, we get:
![3x=2ax\\3=2a\\a=(3)/(2)=1.5](https://img.qammunity.org/2021/formulas/mathematics/high-school/quajucn95e16k0hq30n13dqrg2pk5va3o0.png)
Finally, replacing the value of a in the second equation and solving for b, we get:
![4=a^2+b\\4=1.5^2+b\\b=4-1.5^2\\b=4-2.25\\b=1.75](https://img.qammunity.org/2021/formulas/mathematics/high-school/t53wndvw2mvtdsxwuredk5qekdhheqgto2.png)